Shellfish allergens: tropomyosin and beyond. Issue 6 (19th January 2017) - Faber, M. A.; Pascal, M.; El Kharbouchi, O.; Sabato, V.; Hagendorens, M. M.; Decuyper, I. I.; Bridts, C. H.; Ebo, D. G.
Abstract: IgE‐mediated shellfish allergy constitutes an important cause of food‐related adverse reactions. Shellfish are classified into mollusks and crustaceans, the latter belonging to the class of arthropoda. Among crustaceans, shrimps are the most predominant cause of allergic reactions and thus more extensively studied. Several major and minor allergens have been identified and cloned. Among them, invertebrate tropomyosin, arginine kinase, myosin light chain, sarcoplasmic calcium‐binding protein, and hemocyanin are the most relevant. This review summarizes our current knowledge about these allergens.